A practical rockfall risk model for open pit mines using the time–space concept - Venter, J; Hamman, ECF (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
A number of papers have recently dealt with the topics of economic risk and safety risk in open pits based on larger scale instabilities with more latency (warning time). Rockfall is, however, a low latency failure mechanism and as such, requires separate treatment. This paper presents a practical approach to quantifying rockfall risk based on real measurable data, which allows the model to be calibrated over time. A model is presented that readers can apply in software such as Microsoft Excel and to demonstrate, a practical example is provided. The practical example quantifies the risk for a real slope with and without controls, and demonstrates how factors such as rockfall fences, batter berm configurations, personnel exposure and vehicles can be accounted for to optimise slope design.
Keywords: rockfall risk model